2001
DOI: 10.1002/1097-0142(20010115)91:2<302::aid-cncr1002>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole body positron emission tomography in the treatment of Hodgkin disease

Abstract: BACKGROUND In Hodgkin disease (HD), accurate assessment of the extent of disease is essential because it provides the basis for different treatment strategies. In addition to conventional imaging methods (CIM), positron emission tomography with fluorine‐18‐fluorodeoxyglucose (FDG‐PET) may permit reliable differentiation between lymphoma and nonmalignant tissue and thus improve determination of the stage of the disease. The aim of the current study was to assess the clinical value of FDG‐PET for primary staging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(31 citation statements)
references
References 23 publications
1
27
1
2
Order By: Relevance
“…Weihrauch et al (2002) reported a similar experience in their prospective study mentioned above, in which 18 F-FDG-PET missed Hodgkin's foci in six patients (27%). Although inflammatory lesions, in particular, can cause a pitfall in PET imaging, we did not observe any false-positive PET findings that suggested erroneous upstaging in our study (Moog et al, 1998a;Hueltenschmidt et al, 2001;Naumann et al, 2002a).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Weihrauch et al (2002) reported a similar experience in their prospective study mentioned above, in which 18 F-FDG-PET missed Hodgkin's foci in six patients (27%). Although inflammatory lesions, in particular, can cause a pitfall in PET imaging, we did not observe any false-positive PET findings that suggested erroneous upstaging in our study (Moog et al, 1998a;Hueltenschmidt et al, 2001;Naumann et al, 2002a).…”
Section: Discussioncontrasting
confidence: 56%
“…However, this did not translate into changes in treatment strategy (Jerusalem et al, 2001). In the study of Hueltenschmidt et al (2001) there was a change in treatment in two cases (8%), one of which entailed intensification and one a minimisation of treatment. In the prospective study of Menzel and colleagues, a correct change in stages resulted in six out of 28 (21%) patients (Menzel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Al tener similares resultados que la biopsia de médula ósea, la PET-FDG podría utilizarse en sustitución de esta técnica invasiva, que, por otro lado, presenta en algunos casos falsos negativos. En otros casos la PET-FDG serviría de guía para indicar el lugar más favorable a biopsiar y reducir el número de biopsias negativas [56][57][58][59][60][61][62][63][64][65][66][67][68] . Actualmente, los criterios de indicación de la PET en los linfomas son 1, 2 :…”
Section: Linfomasunclassified
“…Owing to enhancement of the uptake of the radiotracer 18 F-fluorodeoxyglucose ( 18 F-FDG), not only is it feasible to detect even slight neoplastic areas that are imperceptible on CT scans, but residual masses can also be investigated ( Fig. 1) [10]. An interim PET-CT carried out after two or three cycles of chemotherapy helps to evaluate the response to current treatment, and therefore allows for adjustment of the therapy to the individual case, if required.…”
mentioning
confidence: 99%